2022
DOI: 10.3389/fonc.2022.923641
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation-Related LncRNAs Signature for Prognosis and Immune Response Evaluation in Uterine Corpus Endometrial Carcinoma

Abstract: BackgroundsUterine corpus endometrial carcinoma (UCEC) is one of the greatest threats on the female reproductive system. The aim of this study is to explore the inflammation-related LncRNA (IRLs) signature predicting the clinical outcomes and response of UCEC patients to immunotherapy and chemotherapy.MethodsConsensus clustering analysis was employed to determine inflammation-related subtype. Cox regression methods were used to unearth potential prognostic IRLs and set up a risk model. The prognostic value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…As the standard clinical biomarkers, PD-L1 and TMB are imperfect owing to the dynamic alteration during the course of tumors. Non-coding RNA such as lncRNA or circRNA has been screened to predict immune response in many tumor types [ [38] , [39] , [40] ], exhibiting a strong advantage owing to their easy testability. Enhancers have emerged as an important feature for tumors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the standard clinical biomarkers, PD-L1 and TMB are imperfect owing to the dynamic alteration during the course of tumors. Non-coding RNA such as lncRNA or circRNA has been screened to predict immune response in many tumor types [ [38] , [39] , [40] ], exhibiting a strong advantage owing to their easy testability. Enhancers have emerged as an important feature for tumors [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, many studies show that lncRNAs are critical in HNSCC occurrence, and can both promote and suppress cancer. More importantly, some lncRNAs can serve as biomarkers and treatment targets for HNSCC and can predict patient prognosis [2,54,55]. However, as the significant member involved in transcriptional and posttranscriptional regulation, the adjusting role of aging by lncRNAs in HNSCC is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of genomics, a growing number of genetic markers have been uncovered, and these biomarkers have dramatically contributed to cancer research in terms of diagnosis, treatment and prognosis assessment. [18][19][20] In our project, we explored the significance of PRGs in CC utilizing two independent CC cohorts to exploit new prognostic biomarkers and further build a PRG-related signature for predicting the outcome of CC samples. Our results provided data revealing the potential functional and prognostic capabilities of the signature in Previous studies have reported PEG3 plays a central part in p53 regulated cell death, suggesting it may serve as a potential tumor suppressor.…”
Section: Discussionmentioning
confidence: 99%
“…Biomarkers can be used as indicators of pathogenesis or response to therapeutic intervention. With the advancement of genomics, a growing number of genetic markers have been uncovered, and these biomarkers have dramatically contributed to cancer research in terms of diagnosis, treatment and prognosis assessment 18–20 …”
Section: Discussionmentioning
confidence: 99%